2017
DOI: 10.1080/16546628.2017.1341808
|View full text |Cite
|
Sign up to set email alerts
|

Acute fiber supplementation with inulin-type fructans curbs appetite sensations: a randomized, double-blind, placebo-controlled study

Abstract: Background: Research points to a benefit of inulin fiber on appetite and weight regulation but results remain mixed. Objectives: To test the impact of 16 g/d of Inulin-type fructans (ITFs) on appetite and food intake in acute settings.Design: Forty college age females received either a fiber drink with 16 g of ITFs in 330 ml water or placebo. On the 8th day of the study, appetite sensations were assessed using visual analogue scale (VAS) along with food intake. Repeated-measures ANOVA were performed comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Three weeks after subjects returned to their usual diets, these effects were further strengthened, and the desire to eat very sweet and fatty food was significantly decreased. This is in line with recent studies showing that isolated ITF and oligofructose supplementation increases satiety (37) and fullness (38), and decreases reported levels of hunger (10), prospective food consumption (37, 38), and desire to eat fatty, sweet, and salty food (39). Thereby, we show for the first time that an ITF-rich diet has a long-lasting effect on appetite-related sensations.…”
Section: Discussionsupporting
confidence: 91%
“…Three weeks after subjects returned to their usual diets, these effects were further strengthened, and the desire to eat very sweet and fatty food was significantly decreased. This is in line with recent studies showing that isolated ITF and oligofructose supplementation increases satiety (37) and fullness (38), and decreases reported levels of hunger (10), prospective food consumption (37, 38), and desire to eat fatty, sweet, and salty food (39). Thereby, we show for the first time that an ITF-rich diet has a long-lasting effect on appetite-related sensations.…”
Section: Discussionsupporting
confidence: 91%
“…For example, reduced fat sausages that were refor-mulated by adding 24 g of inulin had no significant satiety effect from control sausages [65]. However, recent studies show that consuming a diet that contains inulin-rich vegetables or inulin supplements is linked to a higher satiety and fullness feeling, and a decreased hunger and desire to eat fatty, sugary and salty foods [66,67].…”
Section: Hunger Perceptionmentioning
confidence: 99%
“…Adding fibres was easy because of their physicochemical features. The reasons for choosing 6 g as the amount of fibres were not to affect gastrointestinal symptoms (Heap et al, 2016) and to support and add new results to previous studies (Rebello et al, 2014; Salmean, 2017; Zaremba et al, 2018).…”
Section: Methodsmentioning
confidence: 82%
“…Solah et al (2017) reported that using a supplement of PolyGlycopleX® at the recommended dose resulted in a reduction in body weight (kg) and BMI (kg/m 2 ) and reduced the frequency of eating and the intake of white bread (Solah et al, 2017). Furthermore, one study showed that consuming 16 g/d of inulin-type fructans in the morning for seven days after an overnight fast curbed appetite sensations and helped reduce food intake during lunch meals (Salmean, 2017). In another study, it was reported that inulin had potential as a fat replacer in meat products and could help to reduce fat and EI in men (Archer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%